Modelling and investigation of car collisions - Tautkus, Arūnas; Bazaras, Žilvinas (Transport, 2007)
While investigating collisions with immovable obstacles it is necessary to assess the place of contact, its character and the speed of vehicles before the contact. These parameters depend on the obstacle. The most common cases were analyzed in the article: collision with an immovable obstacle which deformed only a part of the fore of vehicle (collision with a tree, a bollard, etc.); collision with an immovable obstacle which deformed the whole fore of vehicle (collision with a wall, etc.).First Published Online: 27 Oct 2010